1997
DOI: 10.1038/387303a0
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of serotonin-2C receptor G-protein coupling by RNA editing

Abstract: The neurotransmitter serotonin (5-hydroxytryptamine, 5-HT) elicits a wide array of physiological effects by binding to several receptor subtypes. The 5-HT2 family of receptors belongs to a large group of seven-transmembrane-spanning G-protein-coupled receptors and includes three receptor subtypes (5-HT2A, 5-HT(2B) and 5-HT(2C)) which are linked to phospholipase C, promoting the hydrolysis of membrane phospholipids and a subsequent increase in the intracellular levels of inositol phosphates and diacylglycerol. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

33
983
4
6

Year Published

2000
2000
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 949 publications
(1,026 citation statements)
references
References 21 publications
33
983
4
6
Order By: Relevance
“…3a). Emeson and colleagues discovered a total of five A→I RNA editing sites located in the second intracellular loop or G-protein-coupling domain of 5-HT 2C R 55 . Combinatorial editing of the five sites results in changes in three codons, Ile, Asn and Ile, to possibly six different amino-acid residues, resulting in the expression of up to 24 receptor isoforms with altered G-protein-coupling functions.…”
Section: Physiological Significance Of Editing Editing Sites Found Inmentioning
confidence: 99%
See 2 more Smart Citations
“…3a). Emeson and colleagues discovered a total of five A→I RNA editing sites located in the second intracellular loop or G-protein-coupling domain of 5-HT 2C R 55 . Combinatorial editing of the five sites results in changes in three codons, Ile, Asn and Ile, to possibly six different amino-acid residues, resulting in the expression of up to 24 receptor isoforms with altered G-protein-coupling functions.…”
Section: Physiological Significance Of Editing Editing Sites Found Inmentioning
confidence: 99%
“…Q/R-site editing also regulates the tetramerization and intracellular trafficking of the receptor protein 111 . b | Serotonin receptors have important roles in physiological and behavioural processes such as circadian rhythms, emotional control and feeding behaviour 55,64 . G-protein-coupling functions of serotonin (5-HT) receptor-2C (5-HT 2C R) are dramatically reduced by A→I RNA editing that occurs at five sites (A, B, C, D and E sites).…”
Section: Single Nucleotide Polymorphism (Snp)mentioning
confidence: 99%
See 1 more Smart Citation
“…16,17 A limited number of gene transcripts (B30), mostly those that encode channels and neurotransmitter receptors (for example, mammalian glutamate receptors, 5-HT 2C R, potassium channel Kv1.1, and Drosophila melanogaster sodium channel), have been identified to date. [18][19][20][21] When editing occurs within a coding region, it has the potential to alter codon specificity because the ribosome reads inosine as guanosine (G) resulting in altered amino-acid sequence and potentially protein function. In most cases, edited and unedited versions of a given receptor/channel coexist expanding the functional range of the receptor population.…”
Section: Introductionmentioning
confidence: 99%
“…ADAR3 is expressed exclusively in the brain; however, its catalytic substrate has not been identified. 23 5-HT 2C R mRNA is edited at five closely spaced adenosine residues (termed A, B, E, C and D editing sites), allowing for the generation of 32 different mRNA variants and 24 different protein isoforms of the receptor, ranging from the unedited Ile156-Asn158-Ile160 (INI) isoform to the fully edited Val156-Gly158-Val160 (VGV) isoform 18 (Figure 1). Pharmacological studies have shown that the unedited isoform, INI, possesses considerable constitutive activity-an ability to spontaneously activate intracellular signaling pathways in the absence of agonist stimulation.…”
Section: Introductionmentioning
confidence: 99%